Pengaruh Media Pembelajaran terhadap Motivasi Belajar Siswa SMK: Meta Analisis - Zaki, Kaka Ibnu; Iskandar, Ranu; Naryanto, Rizqi Fitri (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to evaluate the effect of learning media on the learning motivation of Vocational High School (SMK) students. The method used in this study is a meta-analysis with data collected through Google Scholar and Semantic Scholar in September 2025. The search keywords used Indonesian with a combination of the variables "learning media" (animation, video, PowerPoint, and teaching modules) and "learning motivation of vocational high school students". The data analyzed were in the form of Effect Size (ES) and Standard Error (SE) values ​​to produce a forest plot containing interval coefficients in each study. Calculations of heterogeneity, publication bias, and fail-safe N were also carried out to ensure the validity of the results. Of the 79 articles searched, 20 articles met the criteria for analysis. The results of the meta-analysis showed that learning media had a significant effect on student learning motivation with a summary effect of 0.849, z = 7.399, p < 0.001, and a 95% CI interval coefficient [0.624; 1.074]. Heterogeneity analysis yielded Q = 1065.072 with p < 0.001 and I² = 97.18% indicating a very high variation between studies. Subgroup analysis based on expertise program showed that Accounting and Finance had a value of -0.161 (95% CI [-0.617; 0.295]), while Automotive Engineering was 0.072 (95% CI [-1.081; 1.225]). Both were insignificant, as p > 0.05. Subgroup analysis based on learning media type also showed insignificant results: animation = 0.225 (95% CI [-1.020; 1.470]), teaching module = -0.125 (95% CI [-0.776; 0.526]), PowerPoint = 0.110 (95% CI [-0.574; 0.794]), and video = 0.215 (95% CI [-0.428; 0.859]). The Egger test showed a p value of 0.662, indicating no indication of publication bias. Furthermore, the fail-safe N value of 10,614 far exceeded the threshold of 110, confirming the reliability of this study. Overall, these findings emphasize the importance of utilizing learning media in increasing vocational high school students' learning motivation, although the effectiveness of specific media types still requires further study.